Implementasi Penilaian Unjuk Kerja dalam Pembelajaran Matematika Berbasis Cooperative Learning Tipe STAD untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas VIII SMP Muhammadiyah 1 Sukoharjo Tahun 2016/2017 - Aprilianti, Gina; , Dr. Sumardi, M.Si (2017)
This research aimed to improve the activity and results of learning mathematics through the implementation of rformance assessment in the based cooperative learning types STAD. The type of the research is qualitative research with the design type action (PTK). These research subjects were 24 students from class VIIIE SMP Muhammadiyag 1 Sukoharjo. The data source consists of a process of learning and assessment. Technique of data in this research is to using the servation method, test, field notes, interviews, and documentation. Data analysis technique was done by means of data reduction, data presentation, and verification of data and making conclusions.The validity of the data using Source Techmic Triangulation. The results showed an increase in activity and student learning outcomes. It can be seen from the increase in the indicators as follows: 1) the courageto put forward the idea of thinging of prior actions (22,73%) to (56,52%) after treatment, 2) courage in asking questions about the material or matter that is not yet understood of prior actions (18,18%) to (69,57%) after treatment, 3) ability in group discussions to resolve the issue in the LKK of prior actions (27,27%) to (78,26%) after treatment, 4) courage work on the problems in front of the class of prior actions (13,63%) to (60,87%) after treatment, and many students who have grades meet KKM (≥ 75) than before treatment (27,27%) to (100%). Conclusion this research is through the implementation of the assessment performance based cooperative learning type STAD can enhance the activity and results of students mathematics learning class VIII E SMP Muhammadiyah 1 Sukoharjo of 2016/2017.